2010
DOI: 10.1017/s0007114510004927
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of garlic, ginger, turmeric and their mixture on hyperglycaemia, dyslipidaemia and oxidative stress in streptozotocin–nicotinamide diabetic rats

Abstract: Spices which show hypoglycaemic, hypolipidaemic and antioxidant activities may have a role in the treatment of diabetes and its complications. The present study aimed to compare the modulatory effects of garlic, ginger, turmeric and their mixture on the metabolic syndrome and oxidative stress in streptozotocin (STZ) -nicotinamide diabetic rats. Diabetes was induced in overnight fasted rats by a single intraperitoneal injection of STZ (65 mg/kg body weight) and nicotinamide (110 mg/kg body weight, 15 min before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 32 publications
(55 reference statements)
9
54
0
3
Order By: Relevance
“…Although several studies have mentioned antidiabetic activity of Zingiber officinale (Grover et al, 2002;Akhani et al, 2005;Kelble, 2005;Al-Amin et al, 2006;Büyükbalci, Sedef, 2008;Islam, Choi, 2008;Abd-Elraheem et al, 2009;Saraswat et al, 2009;Ogbera et al, 2010;Saraswat et al, 2010;Madkor et al, 2011;Ramudu et al, 2011;Rani et al, 2011), no data is available on protein glycation and glucose absorption inhibitory potential of native Zingiber officinale rhizomes at national level. The present study was undertaken to investigate the antidiabetic effects of Zingiber officinale in terms of glucose diffusion and glycation inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have mentioned antidiabetic activity of Zingiber officinale (Grover et al, 2002;Akhani et al, 2005;Kelble, 2005;Al-Amin et al, 2006;Büyükbalci, Sedef, 2008;Islam, Choi, 2008;Abd-Elraheem et al, 2009;Saraswat et al, 2009;Ogbera et al, 2010;Saraswat et al, 2010;Madkor et al, 2011;Ramudu et al, 2011;Rani et al, 2011), no data is available on protein glycation and glucose absorption inhibitory potential of native Zingiber officinale rhizomes at national level. The present study was undertaken to investigate the antidiabetic effects of Zingiber officinale in terms of glucose diffusion and glycation inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…5,10,11 It has also been shown that plant nutrients play protective roles against oxidative stress in diabetic rats. 15,16 The ability of the A. leiocarpus ethanolic leaf extract to protect the rats against oxidative stress could be attributed to its hypoglycaemic principles. [17][18][19][20] The mechanism of action that brings about the hypoglycaemic effect may be by increasing either the pancreatic secretion of insulin from β-cells of the islet of Langerhans or its release from pro-insulin form.…”
Section: Resultsmentioning
confidence: 99%
“…Type 2 diabetes mellitus is related to defects in insulin release or lipid and glucose metabolisms [36] . Prevention and treatment of diabetes are among the priority issues.…”
Section: Pa and Diabetes Mellitusmentioning
confidence: 99%